2017
DOI: 10.1007/s00220-017-3047-y
|View full text |Cite
|
Sign up to set email alerts
|

The Hawking–Penrose Singularity Theorem for C 1,1-Lorentzian Metrics

Abstract: We show that the Hawking-Penrose singularity theorem, and the generalisation of this theorem due to Galloway and Senovilla, continue to hold for Lorentzian metrics that are of C 1,1 -regularity. We formulate appropriate weak versions of the strong energy condition and genericity condition for C 1,1 -metrics, and of C 0 -trapped submanifolds. By regularisation, we show that, under these weak conditions, causal geodesics necessarily become non-maximising. This requires a detailed analysis of the matrix Riccati e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 52 publications
0
66
0
Order By: Relevance
“…Each singularity theorem has a core which relates such causality concepts, and it is this type of result which is preserved. Our generalization is therefore of a different nature with respect to that found in [9][10][11] where the authors assume the stronger C 1,1 regularity but make sense of some other analytical objects entering the classical theorems. Also, we shall not recall the classical versions of the singularity theorems, nor shall we explain in detail why our theorems provide the causality content of such statements.…”
Section: Singularity Theoremsmentioning
confidence: 89%
See 1 more Smart Citation
“…Each singularity theorem has a core which relates such causality concepts, and it is this type of result which is preserved. Our generalization is therefore of a different nature with respect to that found in [9][10][11] where the authors assume the stronger C 1,1 regularity but make sense of some other analytical objects entering the classical theorems. Also, we shall not recall the classical versions of the singularity theorems, nor shall we explain in detail why our theorems provide the causality content of such statements.…”
Section: Singularity Theoremsmentioning
confidence: 89%
“…The problem was solved in [6][7][8] where it was shown that under a C 1,1 differentiability assumption convex neighborhoods do exist and the exponential map provides a local lipeomorphism. From here most results of causality theory follow [6]; Kunzinger and collaborators explored the validity of the singularity theorems under weak differentiability assumption [9][10][11], while the author considered the non-isotropic case [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence the metric (3) is of local Lipschitz regularity in u which is beyond the reach of classical smooth Lorentzian geometry. The latter reaches down to C 1,1 -at least as far as convexity and causality are concerned [16,13,14,5]. However, the Lipschitz property is decisive since it prevents the most dramatic downfalls in causality theory which are known to occur for Hölder continuous metrics [9,3,30,6,17].…”
Section: Introductionmentioning
confidence: 99%
“…In a nutshell, while some features of causality theory are rather robust and topological in nature, other results are usually proved by local arguments involving geodesically convex neighbourhoods, which do exist for C 1,1 -metrics [Min15,KSS14]. Consequently for this regularity class the bulk of causality theory [CG12,Min15,KSSV14] including the singularity theorems [KSSV15, KSV15,GGKS18] remains valid. Moreover, arguments from causality theory which neither explicitly involve the exponential map nor geodesics have been found to extend to locally Lipschitz metrics, see [CG12, Thm.…”
Section: Introductionmentioning
confidence: 99%